Combination of students' strength and aerobic load for successful completion of control standards related to strength endurance - V.V. Poleshchuk; I.N. Poleshchuk; N.S. Bersenev (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the most effective combination of strength and aerobic load of students and evaluate their impact on the level of physical fitness when passing control standards. Methods and structure of the study. The pedagogical experiment was conducted with students of the Tyumen Industrial University Institute of Industrial Technology and Engineering. The students were divided into three groups - two experimental and one control. Each group had its own method of combining power and aerobic exercise. An exemplary program for combining such loads for the successful passing of control standards based on strength endurance is given. Results and conclusions. The dynamics of changes in the results of students, which was observed during one semester, is presented. It is shown that the dynamics of the growth of results in the fulfillment of control standards occurs as a result of the simultaneous development of both power endurance and aerobic endurance. It is noted that the development of aerobic endurance should not be neglected during training in the gym. The growth of results in the implementation of power standards is given by two workouts a week for 30 minutes to develop the aerobic capabilities of the body.